MO211: Variability of Proteinuria in Nephrotic Syndrome: GC1008 PH2 Trial in FSGS. (3rd May 2022) - Lin, Julie; Hariri, Ali; Accomando, Beverly
Abstract: BACKGROUND AND AIMS: Treatment-resistant primary focal segmental glomerulosclerosis (FSGS) is a rare glomerulopathy associated with nephrotic range proteinuria (>3.5 g/24 h). Treatment goals are reduction in proteinuria, which can delay progression to end-stage renal disease. Lack of quality repeated measures data for proteinuria in nephrotic patients is an important methodological limitation in current clinical trials research. METHOD: We examined the 24-h urine collections (traditionally considered to be the gold standard for proteinuria assessment) compared with average of two consecutive first morning spot urine protein/creatinine (Up/c) ratio results for the patients in the placebo arm ( n = 10) of this randomized, double-blind placebo-controlled study (3:3:2 allocation for 1 mg/kg, 4 mg/kg, and placebo treatment groups). Patients received randomized treatment for 112 days and were followed double-blind to 252 days. First morning Up/c was obtained from first morning spot urine collections for all visits; 24-h timed collections were performed for Day 1 and Day 112 visits. For first morning Up/c, the average of two collections at each study time point was used for analysis. RESULTS: Median age was 42 years, 40% female, 20% black, median eGFR 60 mL/min/1.73 m 2 with median Up/c 6.4 g/g (NCT01665391). Correlation coefficient between 24-h timed collection and averaged spot Up/c was r = 0.63 (P = .004). For 24-h timed urines, between subject SD = 2.015 g/24 h and within subject SD = 7.328 g/24 h. For averaged first morning spot Up/c, between subject SD = 2.5 g/g and within subject SD = 2.3 g/g. CONCLUSION: In clinical trials subjects with nephrotic syndrome from biopsy-proven FSGS on stable doses of ACEi/ARB medications, 24-h timed collections do not provide additional useful data beyond average of two first morning spot Up/c. These data suggest that labour intensive, cumbersome timed 24-h urine collections should not be performed in clinical trials of nephrotic syndrome patients. Importantly, these data should allow for more precise power and sample size estimates for future interventional clinical trials of nephrotic syndrome.